Effectiveness of Polyhedrons Multimedia using Articulate Storyline Based on Experientialism Theory Toward Students’ Learning Outcomes and Memory Retention - Santosa, Yoga Tegar; Maulida, Dini Wardani; Murtiyasa, Budi (MaPan : Jurnal Matematika dan Pembelajaran, 2025)
Learning outcomes and memory retention play a crucial role in mathematical learning. However, many students still show low learning outcomes and memory retention, especially in the polyhedron topics. The objective of this study is to examine the effectiveness of multimedia based on Articulate Storyline, oriented to the experientialism theory, student learning outcomes, and memory retention. The study uses a quantitative approach with a quasi-experimental design of the pretest and posttest non-equivalent control group types. The research population is all grade VIII students in one of the Middle schools in Wonosobo Regency. A total of 32 students from class VIII B were assigned as the experimental group, while 32 students from class VIII C served as the control group. The data collection instruments consisted of multiple-choice tests to measure students’ learning outcomes and essays to measure students’ memory retention. Both have been tested for validity and reliability. Data analysis involved the use of inferential and descriptive statistics. The findings revealed that the learning achievements of students in the experimental group were significantly higher than those in the control group. Additionally, the memory retention of students in the experimental group was also superior to that of the control group. These results provide valuable insights for educators and instructional media developers in creating meaningful learning experiences to enhance students’ understanding and memory retention. Abstrak: Hasil belajar dan retensi memori berperan penting dalam pembelajaran matematika. Namun, banyak siswa masih menunjukkan hasil belajar dan retensi memori yang rendah, khususnya pada topik bangun ruang sisi datar. Penelitian ini bertujuan menguji efektivitas multimedia berbasis Articulate Storyline yang berorientasi pada teori eksperiensialisme terhadap hasil belajar dan retensi memori siswa. Penelitian menggunakan pendekatan kuantitatif dengan desain quasi-experimental tipe pretest and posttest non-equivalent control group. Populasi penelitian adalah seluruh siswa kelas VIII di salah satu SMP Negeri di Kabupaten Wonosobo. Sampel terdiri dari 32 siswa kelas VIII B sebagai kelas eksperimen dan 32 siswa kelas VIII C sebagai kelas kontrol. Instrumen pengumpulan data terdiri dari tes pilihan ganda untuk mengukur hasil belajar siswa dan uraian untuk mengukur retensi memori siswa. Keduanya telah diuji validitas dan reliabilitasnnya. Analisis data dilakukan dengan statistik inferensial dan deskriptif. Hasil penelitian menunjukkan bahwa hasil belajar siswa kelas eksperimen lebih tinggi dibandingkan kelas kontrol. Retensi memori siswa kelas eksperimen juga lebih baik dibandingkan kelas kontrol. Temuan ini memberikan implikasi bagi pendidik dan pengembang media pembelajaran dalam merancang pengalaman belajar yang bermakna untuk meningkatkan pemahaman dan daya ingat siswa.